Strategies for Enhancing Quality of Work Life and Their Role in Immunizing the Organization Against Work Alienation: A Field Study at Libya Oil Joint Company – Tripoli. (Al-Farooq Journal of Sciences, 2026)
This study aims to explain how Quality of Work Life (QWL) enhancement strategies can function as a “preventive/protective” mechanism to reduce job alienation among employees of the Libyan Joint Oil Company – Tripoli. The study adopted the descriptive-analytical approach and targeted a population of (220) male and female employees, with a pilot study of (30) conducted to validate the instrument.A questionnaire consisting of (20) items was developed. Reliability (Cronbach’s alpha) reached 0.88 for QWL and 0.85 for job alienation, supporting the validity of the measurement.The results showed that employees’ perceived level of QWL was high, with an overall mean of (2.57), with “physical working conditions/work environment” ranking highest, and a relative gap in “participation in decision-making,” which was at a moderate level.The findings also indicated that the overall level of job alienation was low, with a mean of (1.95); however, the “powerlessness” dimension was relatively the highest.The study confirmed a strong, statistically significant negative correlation between QWL and job alienation (R = -0.82, Sig = 0.000), indicating that improving QWL represents a “protective shield” against alienation.Statistically significant differences also appeared according to years of experience, in favor of less experienced employees (who were more alienated).
Keywords: Quality of Work Life, job alienation, empowerment, participation in decision-making, incentives, Libyan Joint Oil Company, Tripoli